(untitled) (Research, Society and Development, 2024)
Early mobilization in mechanically ventilated patients in the Intensive Care Unit (ICU) is essential to prevent complications, promote faster recovery and reduce mechanical ventilation time. This study aimed to analyze the effects of this practice on adult ICU patients. Searches were carried out in the PEDro, PubMed and SciELO databases, using specific descriptors. Inclusion criteria included free full texts, clinical trials and articles published in the last 10 years. Studies that did not answer the research question were excluded. The search resulted in 25 articles, 05 of which were included in the analysis. The results showed that early mobilization offers significant benefits, such as improved patient mobility, better short- and long-term functional recovery, reduced complications and shorter mechanical ventilation times. The enhanced rehabilitation intervention was associated with specific benefits in terms of early mobilization, physical activity levels and mental health, compared to standard ICU care. The comparison between the groups emphasized the importance of implementing specific strategies to improve the outcomes of critically ill patients on mechanical ventilation. In summary, the studies reviewed show the effectiveness of early mobilization in improving the outcomes and care of ICU patients on mechanical ventilation. The practice promotes better clinical and functional outcomes, highlighting the need for its expansion to benefit a greater number of critically ill patients.